Efficiency Analysis of NACA 4412 Semi-Inverse Taper Wind Turbine For Power Plant - Sulaiman Sulaiman; Asmara Yanto; Ikhsan Febryan (LP2M - Institut Teknologi Padang, 2020)
In this work, a horizontal axis wind turbine (HAWT) are designed and tested to determine turbine efficiency. The wind turbine is built with 3 blades of semi-inverse taper type. This blade is a modification of a type of inverse paper blade that is called semi-inverse taper. This blade is made for moderate wind speeds considering wind in Indonesia. To analyze turbine efficiency, it is necessary to do turbine design and turbine testing stages. From the blade design, the blade radius is 0.9 m. Based on the results of testing and analysis of wind turbine efficiency it can be concluded that the input power and output power are higher with increasing wind speed. However, for the same wind speed, the output power is always smaller than the input power. The increase in input power due to an increase in wind speed is greater than the increase in output power to an increase in wind speed, so the efficiency is lower. The highest wind turbine efficiency was obtained at 84.97% at the lowest wind speed of 5.9 m/s. Whereas at the highest wind speed of 9.3 m/s, turbine efficiency is the lowest at 37.05%.